1999
DOI: 10.1038/sj.mp.4000536
|View full text |Cite
|
Sign up to set email alerts
|

Association of unipolar major depressive disorder with genes of the serotonergic and dopaminergic pathways

Abstract: Keywords: major depressive disorder (MDD); tryptophan hydroxylase (TPH); serotonin transporter promoter region (5-HTTLPR); serotonin receptor 2A (HTR2A); serotonin receptor 2C (HTR2C); catechol-O-methyl transferase (COMT); dopamine D4 receptor (DRD4); dopamine transporter (DAT1)Major depressive disorder (MDD) is a severe psychiatric disorder with a lifetime prevalence of about 15%. 1 The importance of the genetic component is well accepted, 2 but the mode of inheritance is complex and non-Mendelian. A line of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
5
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 18 publications
5
106
5
3
Order By: Relevance
“…The present observations do not support a major role of the COMT val158met variant in the pathogenesis of major depression, confirming previous findings (Kunugi et al, 1997;Frisch et al, 1999;Cusin et al, 2002;Serretti et al, 2003).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present observations do not support a major role of the COMT val158met variant in the pathogenesis of major depression, confirming previous findings (Kunugi et al, 1997;Frisch et al, 1999;Cusin et al, 2002;Serretti et al, 2003).…”
Section: Discussionsupporting
confidence: 78%
“…However, the valine allele appears to be less expressed in the brain as compared to the methionine allele (Bray et al, 2003;Zhu et al, 2004), which slightly mitigates the effect to about 40% increased enzyme activity as conferred by the valine allele (Chen et al, 2004). The COMT val158met polymorphism has repeatedly been investigated for association with major depression with contradictory reports of no association (Kunugi et al, 1997;Frisch et al, 1999;Cusin et al, 2002;Serretti et al, 2003), possible association with the valine allele (Massat et al, 2005;Funke et al, 2005) or conversely the methionine allele (Ohara et al, 1998). Two published studies on the role of the COMT val158met polymorphism in antidepressant treatment response investigating samples of 102 and 346 patients, respectively, report a tentative negative effect of the COMT 158met/met genotype on mirtazapine and citalopram response in major depression (Szegedi et al, 2005;Arias et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Association studies of DRD2 gene polymorphisms and alcoholism or ADHD have suggested that this mechanism might play a role in psychiatric conditions (Comings and MacMurray 2000). However, only one out of eleven other studies investigating the association between 5-HTTLPR and major depression also found that heterozygous subjects are more at risk than the homozygotes, indicating that it is highly unlikely that negative heterosis is present (Bellivier et al 1998;Collier et al 1996;Frisch et al 1999;Furlong et al 1998;Hauser et al 2003;Hoehe et al 1998;Kunugi et al 1997;Mendlewicz et al 2004;Rees et al 1997;Serretti et al 2002;Willis-Owen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Two out of four studies found an increased frequency of the serine variant, indicating that this variant may be associated with major depression (Frisch et al 1999;Lerer et al 2001;Holmes et al 2003;Kö ks et al 2006). 5-HT2C receptor RNA undergoes adenosine-to-inosine RNA modification.…”
Section: -Ht2c Receptormentioning
confidence: 99%
“…5-HT2A receptor polymorphisms are generally not associated with major depression (Zhang et al 1997;Frisch et al 1999;Tsai et al 1999;Minov et al 2001;Oswald et al 2003;Choi et al 2004;Khait et al 2005;Levinson 2005). …”
Section: -Ht Receptorsmentioning
confidence: 99%